Outcomes and predictors of in-hospital mortality among cirrhotic patients with non-variceal upper gastrointestinal bleeding in upper Egypt - Morsy, Khairy H; Ghaliony, Mohamed AA; Mohammed, Hamdy S (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Variceal bleeding is one of the most frequent causes of morbidity and mortality among cirrhotic patients. Clinical endoscopic features and outcomes of cirrhotic patients with non-variceal upper gastrointestinal bleeding (NVUGIB) have been rarely reported. Our aim is to identify treatment outcomes and predictors of in-hospital mortality among cirrhotic patients with non-variceal bleeding in Upper Egypt. Materials and Methods: A prospective study of 93 cirrhotic patients with NVUGIB who were admitted to the Tropical Medicine and Gastroenterology Department, Assiut University Hospital (Assiut, Egypt) over a one-year period (November 2011 to October 2012). Clinical features, endoscopic findings, clinical outcomes, and in-hospital mortality rates were studied. Patient mortality during hospital stay was reported. Many independent risk factors of mortality were evaluated by means of univariate and multiple logistic regression analyses. Results: Of 93 patients, 65.6% were male with a mean age of 53.3 years. The most frequent cause of bleeding was duodenal ulceration (26.9%). Endoscopic treatment was needed in 45.2% of patients, rebleeding occurred in 4.3%, and the in-hospital mortality was 14%. Hypovolemic shock was the most common cause of death (46.2%). Independent risk factors of in-hospital mortality among cirrhotic patients with NVUGIB in our study were bacterial infection during hospitalization [odds ratio (OR) =0.32, 95% confidence interval (CI) =0.03-0.89], shock (OR =1.12, 95% CI =0.68-1.54), early rebleeding (OR =2.26, 95% CI =1.85-3.21), low serum albumin (OR =3.81, 95% CI =2.35-4.67), low baseline hemoglobin (OR =0.714, 95% CI =0.32-1.24), and the need for endoscopic treatment (OR =2.96, 95% CI =0.62-3.63). Conclusion: Bacterial infection during hospitalization, shock, early rebleeding, low serum albumin, low baseline hemoglobin, and the need for endoscopic treatment were independent risk factors of in-hospital mortality among cirrhotic patients with NVUGIB in Upper Egypt.